COVID-19 vaccine equity: a health systems and policy perspective. (2nd January 2022) - Van De Pas, Remco; Widdowson, Marc-Alain; Ravinetto, Raffaella; N Srinivas, Prashanth; Ochoa, Theresa J.; Fofana, Thierno Oumar; Van Damme, Wim
ABSTRACT: Introduction: The global COVID-19 vaccine rollout has highlighted inequities in the accessibility of countries to COVID-19 vaccines. Populations in low- and middle-income countries have found it difficult to have access to COVID-19 vaccines. Areas covered: This perspective provides analyses on historical and contemporary policy trends of vaccine development and immunization programs, including the current COVID-19 vaccination drive, and governance challenges. Moreover, we also provide a comparative health system analysis of the COVID-19 vaccine deployment in some countries from different continents. It recommends that the international Access to COVID-19 Tools Accelerator (ACT-A) partnership requires a strong governance mechanism and urgent financial investment. Expert opinion: All WHO member states should agree on technology transfer and voluntary license-sharing via a commonly governed technology access pool and supported by a just Intellectual Property regime. Contextualized, dynamic understandings and country-specific versions of health systems strengthening are needed to improve vaccine equity in a sustainable matter.